Emergency management in Tahfiz Institutions at Kampung Janda Baik, Pahang - Muhamad Shafiq, Jamaluddin (2019)
This thesis deals with emergency management to improve aspects of safety and health in Tahfiz Institutions at Kampung Janda Baik,Pahang. The background of this studies are according to statistics that released by the Jabatan Bomba dan Penyelamat Malaysia it proved that from year 2015 to 2017 there were 211 fire cases recorded in Tahfiz institution throughout Malaysia, the number of cases has shown that the fire problem that involved the Tahfiz institution was at an alarming level. This problem occur due to the building design and the failure of infrastructural effect of the several Tahfiz institution. With the other hazard that can occur such as a natural hazard are high probability to occur such as landslide, earthquake and flash floods.The main objective of this thesis was to utilize the result of the study in order to improve the emergency management towards the major accident events and knowledge of emergency preparedness. Furthermore, the first objective is to determine vulnerability level Tahfiz intitutions in Kampung Janda Baik The first objective was completed by conducted the vulnerability assessment. From the , assessment it was to identify the potential hazard emerges on the Tahfiz area. The result show there have two type of hazard which is a natural hazard and man-made hazard that are high potentially to occur in the Tahfiz are it is, landslide, earthquake, flash flood, structural fire and open fire. The second objective is to determine the availability of emergency management at Tahfiz Institutions in Kampung Janda Baik,Pahang. The method uses was walkthrough observation and checklist. From the walkthrough observation it to identify the availability of the emergency management system of each Tahfiz. The result show some of Tahfiz are comply with the requirement and standard that are given. The third objective are to measure the level of knowledge on emergency preparedness among student and wardens. From those sources it was identified that the Tahfiz Institutions had high and moderate awareness and knowledge regarding it to emergency preparedness among student and wardens. The method was completed by using questionnaire and survey. In order to increase the preparedness of the Tahfiz institution, some recommendation had been proposed such as by doing OSH in Tahfiz programs which is it can provide the safety education for the Tahfiz community, increase the involvement of the safety practitioner on providing information regarding to safety and health issue it also can provided the safety equipment that are needed to comply with the safety standard for the Tahfiz Institutions. By developing the OSH management system in Tahfiz institutions it can identify the level of safety compliance and there are some of checklist that are provide by PESHA which Systematically OSH Management Enhancement Program (SOMEP) that are provide by PESHA, it because by enhancing SOMEP to the Tahfiz Institutions, based on the result of the checklist we can categories the level of Tahfiz that related and complied with the requirement. By enforcement of the recommendation it can improve the current safety level for the Tahfiz Institutions.